Perkembangan Teknologi Informasi dalam Sistem Informasi Manajemen di Bidang IT - Rida Utami; Nahar Maganda Saragih; Firman Syahputra; Khairul Ummi; Riki Winanjaya; Marlina Manurung (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
Nowadays, most people increasingly perceive information as one of their basic needs besides the need for clothing, food and shelter. Along with this, information changes form into a commodity that has value and can be traded. This situation is proven by the increasing development of the information service business through various media, such as television stations, newspapers, radio and the internet, which have entered many aspects of people's lives. Rapid, dynamic and extensive environmental changes are supported by advances in information technology in almost all fields. This has encouraged changes in the lifestyle of traditional society into an information society. The rapid development of information technology has had an impact on people's lives. Since the discovery of computers in 1955, until now it continues to experience very significant developments. Information technology with computers as one of the very important components has changed the acquisition of information which is now not only from surrounding sources but information that comes from various sources. Computer-based information processing People are starting to become known and up to now there is a lot of software that people can use as a data processing tool to produce the desired information.